2021
DOI: 10.15547/ast.2021.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Implications of captive breeding for the reintroduction of the Saker falcon (Falco cherrug) in Bulgaria

Abstract: Abstract. The Saker falcon (Falco cherrug) is a globally endangered species recovered in 2018 in Bulgaria. The only known active pair currently breeding in the wild in the country is made up of captive-bred and released birds, part of the first reintroduction programme for the species in Bulgaria and globally. As part of the project, sourced Saker falcons of known European origin are bred ex situ, the juveniles are parent-reared and released in the wild by means of the hacking method. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We collected blood samples from birds housed at two different captive breeding facilities: the WRBC of the of Green Balkans–Stara Zagora NGO (31 F. c. cherrug ) and the Breeding Centre for Birds of Prey (BCBP) in Burgas, Bulgaria (68 F. c. milvipes and 13 F. c. cherrug ). Ten of the aviaries at the WRBC measured 4 × 3 × 3 m; and two were 4 × 5 × 3 m (Petrov et al 2021). The aviaries ( n = 34) at the BCBP were 5.5 × 4 × 3.5–4.2 m (range due to difference in terrain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected blood samples from birds housed at two different captive breeding facilities: the WRBC of the of Green Balkans–Stara Zagora NGO (31 F. c. cherrug ) and the Breeding Centre for Birds of Prey (BCBP) in Burgas, Bulgaria (68 F. c. milvipes and 13 F. c. cherrug ). Ten of the aviaries at the WRBC measured 4 × 3 × 3 m; and two were 4 × 5 × 3 m (Petrov et al 2021). The aviaries ( n = 34) at the BCBP were 5.5 × 4 × 3.5–4.2 m (range due to difference in terrain).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 98 captive-reared Saker Falcons were reintroduced into the wilds of Bulgaria in 2015–2021; of these, 81 had hatched in the Wildlife Rehabilitation and Breeding Centre (WRBC) and 17 were imported from other centers. Eighty-two percent of all Saker Falcons that hatched in the WRBC during that period were released using the soft-release hacking method (Petrov et al 2021). The first nesting by released birds was discovered in 2018 (Dixon et al 2020, Lazarova et al 2021), and another nesting territory was found later.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Among the POMs, the area of polyoxovanadate (POV)-based materials has received special attention, which is due not only to their diverse topologies, 11,12 structural 13 and electronic properties 14 but also to their fascinating versatile industrial applications, e.g., in catalysis, 15 materials, 16,17 and biomedicine. 18,19 Their biological activity derives mainly from their redox behaviour, their biomimetic activity, or from their capability to interact with biological macromolecules through electrostatic interactions. 20 Vanadium(IV)-and vanadium(V)based compounds have been tested for their potential biomedical use in the treatment of diabetes mellitus, cancer, bacterial diseases and viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the current stage of the species restoration project is to release 100 juvenile sakers over a five-year period (2020-2024). They are retained in the hack sites until independence through food provision in order to imprint on the area and return to it when they reach breeding age at around 3-years-old ( Dixon et al 2020 , Lazarova et al 2021 , Petrov et al 2021 , Petrov et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%